Evaluating integrated training for juvenile criminal justice system at the national police education and training center - Abraham, Irfan; Ridwan, Ahmad; Triana, Dinny Devy (Institute of Advanced Engineering and Science, 2024)
This study critically assesses the integrated technical training program for the juvenile criminal justice system, conducted by the national police education and training institute in Indonesia. The research employs a mixed-method approach, utilizing an explanatory sequential design and applying the Kirkpatrick evaluation model, involving 62 participants. Content validity is maintained through expert input, with the Aiken v formula employed for result analysis. Credibility is affirmed through a focus group discussion. The study aims to evaluate the program’s impact on the rights of Indonesian children in legal conflicts. Findings indicate participants’ satisfaction and high motivation at level 1 (reaction), while levels 2, 3, and 4 reveal a positive impact on protecting the rights of children involved in legal conflicts. The research highlights the need for a larger sample size and a more extended measurement period for future investigations. Objectives encompass assessing program impact, learning outcomes, behavioral changes, external organizational impact, and examining the program’s practical contribution to educational research and evaluation, guiding recommendations for future improvements.